Financial Market Implications of India's Pension Reform - Poirson, Helene (IMF Working Papers; Working Paper ;, 2007)
India's planned pension reform will set up a proper regulatory framework for the pension industry and open up the sector to private fund managers. Drawing on international experiences, the paper highlights pre-conditions for the reform to kick-start financial development, including: (i) the buildup of critical mass; (ii) sufficiently flexible investment guidelines and regulations, including on investments abroad; and (iii) concurrent reforms in capital markets. Given the limited scale of the planned reform, the key challenge for India is to achieve sufficient critical mass early on. Options to address this challenge include granting permission for existing workers to switch to the new system or outsourcing all or part of the reserves of private sector provident funds to the new pension fund managers.